Diffraction resonance with strong optical-field enhancement from gain-assisted hybrid plasmonic structure - Zhou, Yanyan (2013)
We propose and analyze the diffraction coupling of localized plasmon resonances (LPRs) through gain-assisted propagation surface plasmons (PSPs). The coupling process involves localization of incident light by LPR and LPR-PSP interaction. We demonstrate a significantly strong enhancement of electromagnetic power for LPRs in the event of diffraction resonance through incorporation of experimentally feasible optical gain to the PSP. Based on such phenomenon, we propose a hybrid plasmonic structure, which would potentially give rise to device realization of the nano-lasers. In addition, it is also a promising platform for applications such as surface enhanced Raman scattering, nonlinear optics, plasmonic trapping, etc.